E-learning in the Lebanese Higher Education Institutions: An Assessment of Factors Leading to Students‟ Satisfaction (Asian Business Research, 2021)
The Higher Education Institutions (HEIs) in Lebanon have been heavily impacted since the COVID-19pandemic outbreak. The majority of the institutions had to react to the sudden decision to go online. In fact, theyhad to develop unplanned E-learning programs to assure the academic year‟s survival. In Lebanon, the Ministryof Education & Higher Education (MEHE) has ordered all educational institutions, public and private, to stopphysical learning and start implementing E-learning through various online platforms. Because of Lebanon‟sunprepared infrastructure, students in universities struggled to continue their studies and to keep pace with otherswho have better situations. The purpose of this study is to assess the factors that may impact the success ofE-learning in Lebanese universities and that affect students‟ satisfaction in adapting to this unplanned phase. Thestudy is quantitative, explorative, descriptive and causal. A questionnaire was designed to collect primary datafrom 380 university students belonging to ten universities. Data analysis was carried out using the SPSS version25 software. Several statistical techniques were performed including descriptive statistics and carrying outrelational analysis via Factor Analysis (FA) and linear regression. Five constructs were defined namely, (1)Infrastructure, (2) Computer Skills, (3) E-Learning Content & Autonomy, (4) Support from others, and (5)Satisfaction. Results show that students‟ satisfaction is strongly influenced by the other four internal (2) andexternal (2) factors. Findings will support a set of recommendation directed to decision makers in HEI and theMEHE officials.